2012
DOI: 10.1097/nna.0b013e318274b5d5
|View full text |Cite
|
Sign up to set email alerts
|

Decisional Involvement in Magnet®, Magnet-Aspiring, and Non-Magnet Hospitals

Abstract: Decisional involvement is higher among Magnet-designated than non-Magnet facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 14 publications
1
29
1
6
Order By: Relevance
“…Houston et al (2012) found a statistically significant difference in actual global scores in DI between Magnet, Magnet-aspiring, and non-Magnet facilities. The Magnet hospitals' DI scores were statistically higher than the other two types of facilities (Houston et al, 2012). Thus, it is necessary for organizations not only to provide nurses the opportunity to be involved in decision making but also to provide the structure for advancement of nurses.…”
Section: Of Staff Nursesmentioning
confidence: 89%
“…Houston et al (2012) found a statistically significant difference in actual global scores in DI between Magnet, Magnet-aspiring, and non-Magnet facilities. The Magnet hospitals' DI scores were statistically higher than the other two types of facilities (Houston et al, 2012). Thus, it is necessary for organizations not only to provide nurses the opportunity to be involved in decision making but also to provide the structure for advancement of nurses.…”
Section: Of Staff Nursesmentioning
confidence: 89%
“…28 Other studies identified positive associations between ANCC Magnet recognition and/or Magnetaspiring hospitals and nurse outcomes such as empowerment, involvement in decision making, efficiencies in operations, job satisfaction, and turnover intentions, as well as on patient outcomes such as mortality. [29][30][31][32][33] Productive WardYReleasing Time to Carei, also known as The Productive Ward (PW), was developed by the National Health Service (NHS) Institute for Innovation and Improvement and launched in England in 2007. Specifically, it is a quality improvement program designed to provide staff with more time to provide direct patient care.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7] Magnet hospitals have achieved superior financial performance and nursing satisfaction metrics. 1,[22][23][24][25][26] However, the association of this recognition with the outcomes of neurosurgical procedures has not been studied before.…”
Section: Discussionmentioning
confidence: 99%
“…Magnet hospitals have been found to have higher nursing satisfaction and autonomy, less organizational hierarchy, and are prone invest in quality benchmarking and reporting. 1,[22][23][24][25][26][32][33][34] Such institutional commitment to quality improvement empowers nurses and physicians to deliver evidence-based care, establish effective communication, and identify patient problems quicker. [32][33][34] When focusing on policy development, it is important to recognize such effective initiatives, given the growing body of public reporting.…”
Section: Discussionmentioning
confidence: 99%